The Political Independence of the Working Class: Antonio Gramsci’s Pedagogical Leitmotif - John D. Holst (Adult Education Research Conference, 2015)
This paper argues that the leitmotif of Gramsci’s theory and practice was the political independence of the working class. The centrality of pedagogy in this leitmotif is captured by Gramsci’s concept of catharsis.
Keywords: radical adult education; Gramsci; working class